An Energy-Efficient and Reliable Opportunistic Routing for Wireless Sensor Networks - Kumar, Nagesh; Singh, Yashwant (International Journal of Sensors Wireless Communications and Control, 2021)
Background: Routing protocols in Wireless Sensor Networks (WSN) are of major concern because of the important factors like energy efficiency and reliability. Opportunistic Routing (OR) is the simplest and reliable routing technique for ad-hoc networks and WSN. The OR protocol guarantees data delivery in the network. As WSN need energy-efficient routing, therefore, energy- efficient OR protocols gained popularity in the last three years. Objectives: Opportunistic routing improves the performance of the network by utilizing the broadcasting abilities of wireless channels. In this paper, a new energy-efficient and reliable routing protocol has been proposed that is based on the opportunistic routing technique. Methods: The proposed protocol is based on the energy-efficient routing metric. The proposed OR protocol prioritizes among the candidate forwarders on the basis of energy-efficient routing metric and this will lead to the achievement of improved network lifetime. Results: The end-to-end delay is reduced because of the selection of candidate forwarders from the neighbor list of each node. The proposed protocol uses selective acknowledgment mechanisms. The simulation results of the proposed protocol depict the improved performance as compared to other recent OR protocols. Conclusion: The proposed protocol can directly be used with existing WSN applications. Further improvements can be made by utilizing more parameters like distance and the quality of transmission.
Keywords: opportunistic routing